PELAKSANAAN PUTUSAN VERSTEK DALAM PERKARA GUGATAN SEDERHANA NOMOR 17/PDT.G.S/2023/PN.PTK - NIM. A1012201089, SYARIFAH ELVANI APRILIANI ALKADRIE (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract The individual who provided the loan was Mr. Ivan Agustinus, with debts and receivables totaling IDR 30,000,000.00. In this instance, Mr Mulyadi has defaulted by only fulfilling his borrower responsibilities in line with what the parties had agreed upon. Subsequently, the case proceeded until the conclusion of decision No. 17/PDT.G.S/2023 PN.PTK, wherein Mr. Mulyadi is the defendant and Mr. Agustinus is the plaintiff. The problem is stated as follows: